(untitled) (ALPHA. Journal of Arts, Literature and Philosophy, 2017)
We present a recovery of the humanistic spirit in the current aesthetics of the media art in the cybercultures. To show the cultural shift towards Neo-Renaissance, we tour the concepts underlying the classical humanism and contemporary art closer to technologic and mediatic rationality. This article reviews the meeting of man with himself, the subjectivities of the Art and the expression in the paradigm of new technologies, science and creativity, as well as the renewal of an emerging visual epistemology that moves the modern concept of the work of art, the figure of the artist and the place of the viewer.